Phonological redeployment for [retracted tongue root] in third language perception of Kaqchikel stops - Nelson, Brett C. (Frontiers in Language Sciences, 2023)
Phonological redeployment is the theoretical ability of language learners to utilize non-local phonological knowledge from known languages in the mapping and acquisition of novel contrasts in their target languages. The current paper probes the limits of phonological redeployment in a third language acquisition scenario.The phonological features [Advanced Tongue Root] and [Retracted Tongue Root] capture a range of phonological contrasts and harmony processes in both vowels and consonants of spoken languages across the world, including, but not limited to, vowel tensing and post-velar places of articulation (e.g. uvular). Kaqchikel (cak) exhibits both a tense-lax vocalic contrast in its vowels plus a velar-uvular Place contrast in its eight stop consonant phonemes. English (eng) exhibits a tense-lax vocalic distinction but no velar-uvular distinction among its six stop phonemes. Spanish (spa) exhibits neither of these contrasts in its vowels or among its six stop phonemes. How do multilingual learners of Kaqchikel already familiar with English and Spanish, but who differ in which is their first language (L1), compare in their categorical perception of Kaqchikel stop consonants? Despite English and Spanish having a three-way Place distinction among stops in common, L1 English learners of Kaqchikel were better at correctly categorizing audio recordings of Kaqchikel uvular stops than the L1 Spanish learners. To account for this surprising result, I propose that the L1 English group have easier access than the L1 Spanish group to the feature underlying English's tense-lax distinction. This access allows them to redeploy that phonological feature to accurately map out the novel four-way contrast of Kaqchikel's stop consonants, and the [±RTR]specified velar-uvular distinction in particular. Therefore, phonological redeployment must be considered in models of third language acquisition.